Risk assessment of time and cost overrun factors throughout construction project lifecycle - Ismail, Ismaaini (2014)
Construction industry is a very important industry for the economic development of the country. However, this industry has been facing serious problems i.e. failure to complete projects within stipulated time and cost. Hence, the aim of this study is to assess the risk of various factors that cause time and cost overruns throughout the life cycle of construction projects in Malaysia. A total of 35 factors were identified from previous studies. The data collections were carried out using structured questionnaire survey. A pilot study was conducted to determine the level of occurrence and severity of each factor with respect to various phases of project life cycle. Then, the actual survey was conducted in two rounds of Delphi. Delphi round 1 was conducted to assess the probability of occurrence and level of severity of each factor in the life cycle phases. Based on the survey, construction phase was found as the phase that had significantly contributed to time and cost overrun compared to other phases. Then, Delphi round 2 was conducted to seek agreeability from respondents regarding the results obtained from the Delphi round 1. The result showed that majority of respondents had agreed with the results from Delphi round 1. This study found that there were 12 high risk factors on time overrun, namely: poor site management and supervision, incompetent subcontractors, inadequate planning and scheduling, frequent design changes, mistakes and errors in design, change in the scope of the project, delay preparation and approval of drawings, lack of coordination between parties, slow information flow between parties, lack of communication between parties, shortages of materials, and late delivery of materials and equipment. While, there were 9 high risk factors on cost overrun, namely: poor site management and supervision, incompetent subcontractors, schedule delay, inaccurate time and cost estimates, mistakes during construction, incomplete design at the time of tender, poor design and delays in design, contractual claims, such as, extension of time with cost claims, and poor financial control on site.